Does the use of pharmacotherapy interact with the effects of psychotherapy? A meta-analytic review - Cuijpers, Pim; Miguel, Clara; Harrer, Mathias; Ciharova, Marketa; Karyotaki, Eirini (European Psychiatry, 2023)
Background: It is not clear if there is an interaction between psychotherapy and pharmacotherapy. First, there may be no interaction at all, meaning that the effects of both are independent of each other. Second, antidepressants may reduce the effects of psychotherapy, and third, antidepressants may increase the effects of psychotherapy. We examined which of the three is correct in a large meta-analysis. Methods: We conducted random effects meta-analyses of randomized trials comparing psychotherapies for adult depression with control conditions. The proportion of users of antidepressants was used as predictor of the effect size in a series of meta-regression analyses, while adjusting for relevant moderators, such as type of control group and baseline severity. Results: We included 300 randomized controlled trials (353 comparisons between treatment and control; 32,852 participants). The main effect size of psychotherapy was g= 0.71 (95% CI: 0.64; 0.79) with high heterogeneity (I2=82; 95% CI: 80; 84). We found no significant association between the proportion of antidepressants users and effect size (p=.07). We did find a significant association with some other predictors, including the type of control group and risk of bias. The use of antidepressants was associated with higher response rates within the control conditions, but not with the relative effects of the treatments compared to the control groups. Discussion: We found support for independent effects of psychotherapy and pharmacotherapy, which is good news from a clinical perspective. Apparently, patients can start with psychotherapy and do not have to be afraid that this will reduce the effects of the therapy.
CRIS-Team Scopus Importer:2023-09-01
Keywords: antidepressants; depression; meta-analysis; psychotherapy